Long non-coding RNA SNHG14 promotes microglia activation by regulating miR-145-5p/PLA2G4A in cerebral infarction. (21st April 2017) - Qi, Xu; Shao, Ming; Sun, Hongjing; Shen, Yue; Meng, Delong; Huo, Wei
Highlights: SNHG14 highly expressed in ischemic cerebral tissues and BV-2 cells after OGD. SNHG14 induced the activation of MCs by regulating miR-145-5p/PLA2G4A axis. The findings added new contents to the pathogenesis of cerebral infarction. Abstract: Activated microglia cells (MCs) are able to release a large amount of inflammatory cytokines after ischemic stroke, which exacerbates neuron damage. In this study, we explored the functional involvement of long non-coding RNA (lncRNA) SNHG14 and its potential regulatory mechanism in the activation of MCs. The mouse model of middle cerebral artery occlusion (MCAO) and microglia cell model of oxygen/glucose deprivation (OGD) were made. The expression of SNHG14, miR-145-5p and PLA2G4A protein expression was determined by quantitative real time PCR and western blot, respectively. Dual-luciferase assay was used to verify the direct binding of miR-145-5p and PLA2G4A. Flow cytometry was applied to measure neurons' apoptosis. SNHG14 highly expressed in ischemic cerebral tissues and BV-2 cells after OGD treatment. SNHG14 knockdown could remarkably inhibit BV-2 cells activation induced by OGD; while SNHG14 overexpression significantly promoted BV-2 cells activation, showing an increase of TNF-α and NO production and neurons' apoptosis rate. Additionally, SNHG14 knockdown promoted the expression of miR-145-5p and reduced PLA2G4A. Contrarily, SNHG14 overexpression inhibited miR-145-5p expression and increased PLA2G4A. Moreover, miR-145-5p overexpression also reversed the effect of OGD on BV-2 cells activation. Bioinformatics analysis and dual-luciferase assay supported that SNHG14 could bind directly to miR-145-5p and miR-145-5p-binding site was existed on 3′-UTR of PLA2G4A. MiR-145-5p mimic reversed the increase of PLA2G4A and reduced the high levels of TNF-α and NO in BV-2 cells induced by SNHG14 overexpression. SNHG14 increased the expression of PLA2G4A by inhibition of miR-145-5p, which resulted in the activation of MCs in cerebral infarction.